Iridoid esters from Valeriana pavonii Poepp. & Endl. as GABAA modulators: Structural insights in their binding mode and structure-activity relationship - Sara E. Giraldo; Mauricio Bedoya; Carlos Peña-Varas; Paula A. Santana; Isabel L. Bazzocchi; Ignacio A. Jiménez; Mariel Marder; Nadezdha E. Vergel; Mario F. Guerrero; David Ramírez (GarVal Editorial Ltda., 2023)
Context: Valeriana pavonii Poepp. & Endl. (Caprifoliaceae), is a plant used in traditional medicine as a tranquilizer in Colombia. Valerian extracts have been widely used since ancient times for their sedative and anxiolytic properties; however, the way its active metabolites, including iridoids, interact on their respective targets is not fully understood. Aims: To isolate and identificate active iridoid esters from V. pavonii. Perform in vitro inhibition assays and computational analyses to study their possible interaction on the benzodiazepine site of the GABAA receptor. Methods: Two compounds were obtained from dichloromethane and petroleum ether fractions of V. pavonii, respectively, by chromatographic techniques. The structural elucidation was performed by NMR and spectroscopic analyses. In vitro inhibition assays of the binding of 3H-flunitrazepam (3H-FNZ) for the benzodiazepine binding site of the GABAA receptor (BDZ-bs of the GABAA receptor) were carried out. Results: Two iridoid esters, hydrine-type valepotriates (compounds 1 and 2), were reported for the first time in V. pavonii. Both iridoids, 1 and 2, inhibited the binding of 3H-FNZ on the BDZ-bs of the GABAA receptor (40% at 300 µM). Docking studies and MMGBSA calculations revealed that these compounds exhibited molecular interactions with crucial residues of the benzodiazepine site, similar to those observed for drugs like flunitrazepam, diazepam, and flumazenil. Conclusions: These findings contribute to understanding the in vivo activity of extracts of Valeriana pavonni on the central nervous system, which showed promising effects, especially as anticonvulsants, sedative-hypnotics, and antidepressants, through the modulation of the GABAergic system by hydrine-type valepotriates and its derivatives.